Regulation of p53 Target Gene Expression by Peptidylarginine Deiminase 4 - Li, Pingxin (American Society for Microbiology (ASM), 2008)
Histone Arg methylation has been correlated with transcriptional activation of p53 target genes. However, whether this modification is reversed to repress the expression of p53 target genes is unclear. Here, we report that peptidylarginine deiminase 4, a histone citrullination enzyme, is involved in the repression of p53 target genes. Inhibition or depletion of PAD4 elevated the expression of a subset of p53 target genes, including p21/CIP1/WAF1, leading to cell cycle arrest and apoptosis. Moreover, the induction of p21, cell cycle arrest, and apoptosis by PAD4 depletion is p53 dependent. Protein-protein interaction studies showed an interaction between p53 and PAD4. Chromatin immunoprecipitation assays showed that PAD4 is recruited to the p21 promoter in a p53-dependent manner. RNA polymerase II (Pol II) activities and the association of PAD4 are dynamically regulated at the p21 promoter during UV irradiation. Paused RNA Pol II and high levels of PAD4 were detected before UV treatment. At early time points after UV treatment, an increase of histone Arg methylation and a decrease of citrullination were correlated with a transient activation of p21. At later times after UV irradiation, a loss of RNA Pol II and an increase of PAD4 were detected at the p21 promoter. The dynamics of RNA Pol II activities after UV treatment were further corroborated by permanganate footprinting. Together, these results suggest a role of PAD4 in the regulation of p53 target gene expression.